Analisis Hukum Islam Terhadap Pelaksanaan Mediasi Perkara Perceraian di Pengadilan Agama Gedong Tataan dan Pengadilan Agama Pringsewu Lampung - Mutholib, Mutholib; Faizal, Liky; Zaki, H. Muhammad (Fakultas Syariah INSURI Ponorogo, 2022)
Mediation in Islam is known as Islâh and hakam. When a dispute or dispute occurs, the disputing parties make peace efforts by appointing a judge. In the case of divorce, the function and efforts to reconcile are the obligations of the judge as a mediator which must be carried out based on Supreme Court Regulation no. 01 of 2016 concerning Mediation Procedures in Courts. Therefore, peace efforts are sought through mediation in the Religious Courts so that couples who want to divorce cancel their intentions and reconcile. However, the reality is that the success rate of mediation in divorce cases is still relatively low. This is evidenced by the number of cases that end in the trial process, compared to the success of the Mediation process. The purpose of this study was to analyze the implementation of divorce case mediation based on Perma No. 1 of 2016. As well as analyzing Islamic law on the implementation of mediation in divorce cases at the Gedong Tataan Religious Court and the Pringsewu Religious Court. The method used in this research is descriptive qualitative with theological, juridical normative and sociological approaches, with the object of research being the Gedong Tataan Religious Court and the Pringsewu Religious Court in Lampung. The primary data in this study were obtained from interviews with the Mediator Judge. The secondary data used is the report on the success and failure of the mediation implementation recorded in the final report and the Case Investigation Information System (SIPP). The results obtained from the research that the implementation of mediation at the Gedong Tataan and Pringsewu Religious Courts, based on PERMA No. 1 of 2016, but the implementation of mediation cannot be said to be optimal or not effective, because the success of mediating divorce cases is still relatively low. Mediation or Islah in resolving domestic conflicts actually contains benefits, namely maintaining the objectives of Islamic law (maqasid al-syariah), namely maintaining religion, soul, mind, lineage, and property. Maqashid sharia in mediation is hifd al-nasl (keeping offspring)